Pengaruh Isu Bullying Terhadap Kepercayaan Orang Tua Pada Pesantren di Kota Tanjung Pinang - Anggraini, Resita; Khatijah, Siti (Huma: Jurnal Sosiologi, 2024)
Bullying cases that are often heard and occur in educational environments, including in Islamic educational institutions or pesantren, are a worrying phenomenon because of the impact of the bullying. This research aims to find out how the level of trust of parents in sending their children to pesantren with various news related to bullying cases in pesantren. The research method used is qualitative with a descriptive approach to describe and describe the problems studied. The research was conducted for 2 months, namely from May to June 2024. The theory used in this research is the Rational Choice Theory proposed by Jame S Coleman, which suggests that choice does not focus on what is chosen or what is the source of choice, but rather on the fact that it is believed that actions are taken as goals that are in accordance with the level of choice. The results showed that the pattern of violence committed by the bully was the same as what he had experienced, indicating that this culture has been attached and even become a stigma for santri. Various news about bullying in pesantren affect parents' confidence to send their children to pesantren. However, many parents still believe that pesantren is the best place to educate their children. Parents consider good education and the formation of their children's personality in the field of religion. It is important for parents to learn more and be selective in choosing pesantren to ensure their children's safety from the threat of bullying.